Clusters in Atoms and Nuclei - Anagnostatos, G. S. (HNPS Advances in Nuclear Physics, 2020)
Small aggregates of particles, possessing different properties than those in bulk (i.e., in crystals or in nuclear matter), are reviewed here. Specifically, while some categories of atomic clusters (regular or bosonic) are in a solid state of matter and their structure possesses, more or less, definite geometric picture of packing of spheres standing for atoms, some other categories of atomic clusters (quantum or fermionic) are in a liquid (or gas) state of matter and their structure follows quantum mechanics whose only the average forms have a geometrical representation. These quantum clusters can be extended to include nucléon clusters of spheres standing for the nucléon bags with rather impressive results. All families of clusters considered together could be seen as a fifth state of matter.